Recent Insights into Muscle Fatigue at the Cross-Bridge Level - Debold, Edward (Frontiers in Physiology, 2012)
Muscle fatigue is a complex multi-factorial process in humans that is dependent on the mode and intensity of the contractile activity. The depression in force and/or velocity associated with fatigue can be the result of a failure at any level, from the initial events in the motor cortex of the brain to the formation of an actomyosin cross-bridge in the muscle cell. Factors distal to the neuromuscular junction appear to be most important for fatigue resulting from intense contractile activity. Given that all the force and motion generated by muscle ultimately derives from the cyclical interaction of actin and myosin, researchers have focused heavily on the impact of the accumulation of intracellular metabolites (e.g. Pi, H+ and ADP) on the function these contractile proteins. These efforts demonstrate when elevated to the levels reached during intense contractile activity these metabolites can significantly alter a muscles’ force and motion generating capacity. At saturating Ca++ levels, elevated Pi appears to be the primary cause for the loss in maximal isometric force, while increased [H+] and possibly ADP act to slow unloaded shortening velocity. These studies, performed on isolated muscle preparations, provided strong evidence that these metabolites play a causative role in muscular fatigue, however the precise mechanisms through which these metabolites might affect the individual function of the contractile proteins remains unclear because intact muscle is a highly complex structure with the observed contractile properties representing the collective action of billions of myosin molecules. Fortunately more recent experiments on isolated proteins, including some single molecule measurements, are giving us unprecedented insight into the molecular processes that may be at work during fatigue. For example, using isolated actin and myosin in an in vitro motility assay, researchers have demonstrated decreasing pH from a resting level ( 7.0) to a level reache